2020
DOI: 10.1002/ab.21916
|View full text |Cite
|
Sign up to set email alerts
|

Twin study of laboratory‐induced aggression

Abstract: The aim of this study was to explore genetic and environmental contributions to laboratory-induced aggressive behavior. On a sample of 478 adult twins (316 monozygotic), the Competitive Reaction Time Task was used for aggression induction. The results showed that the initial, basic level of aggression could be explained by both shared (45%) and nonshared environmental factors (55%), while only nonshared environmental factors (100%) had a significant influence on changes in aggression as provocation increased. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…In line with previous research (Anderson et al, 2008;Weidler et al, 2019;Dinić et al, 2020;Konzok et al, 2020), we anticipate that the mean level of aggression among sibling pairs will increase across trials and blocks, with the highest levels of aggression occurring 10.3389/fpsyg.2024.1288743 after the fake block in the center. Building on prior findings (Weidler et al, 2019), we hypothesize that gender will influence overall aggression and distinctly modulate the aggression trajectory across blocks differently.…”
Section: Hypothesessupporting
confidence: 84%
See 2 more Smart Citations
“…In line with previous research (Anderson et al, 2008;Weidler et al, 2019;Dinić et al, 2020;Konzok et al, 2020), we anticipate that the mean level of aggression among sibling pairs will increase across trials and blocks, with the highest levels of aggression occurring 10.3389/fpsyg.2024.1288743 after the fake block in the center. Building on prior findings (Weidler et al, 2019), we hypothesize that gender will influence overall aggression and distinctly modulate the aggression trajectory across blocks differently.…”
Section: Hypothesessupporting
confidence: 84%
“…Furthermore, it is necessary to investigate whether the observed trend in gender differences persists in non-sibling pairs and opposite-sex pairs or is specific to dynamics within same-sex sibling pairs. Other evidence supporting the influence of sibling gender on aggression dynamics comes from a study on aggressive behavior of twins which used the TAP procedure ( Dinić et al, 2020 ). Sisters from opposite-sex twin pairs exhibited more aggression toward their male twin counterparts compared to women in same-sex dyads from the control group of strangers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides self-report measures, differences between MZ twins in aggression was identified in specific aggressive behavior measured by experimental CRTT procedure as unprovoked direct aggression. Previous research using CRTT showed that shared and non-shared environmental factors, without genetic influences, almost equally contributed to the explanation of the initial level of aggression (Dinić et al, 2020) which could be linked to aggression in the 1st block of the CRTT scale. Thus, unprovoked aggression is partly influenced by the learned patterns developed in a shared, family environment.…”
Section: Discussionmentioning
confidence: 99%
“…Before each task, each twin had an opportunity to set the "punishment" for his/her twin pair. The punishment consisted of the settled intensity (on a scale from 0 = no punishment, 1 = 60 db to 10 = 105 db) and duration of an aversive noise (on a scale from 1 = 0.5 s to 10 = 5 s, see Dinić et al, 2020). After the punishment was established, the researchers began the competition.…”
Section: Competitive Reaction Time Taskmentioning
confidence: 99%